The New ‘Aisyahs: A Comparative Political Analysis of Female Muslim Legislators and Gender-Inclusive Policies in Indonesia and Turkey - Murat Arslan; Cemil Kaya; Hale Yilmaz (Islamic Studies in the World, 2025)
Female Muslim legislators have become increasingly visible in the political landscapes of several Muslim-majority countries, including Indonesia and Turkey, where shifting democratic norms and evolving interpretations of Islamic gender ethics shape women’s participation in governance. Despite expanded representation, questions remain regarding how these women influence gender-inclusive policymaking and how their political strategies differ across distinct socio-religious and institutional contexts. Understanding these dynamics is essential for analyzing the broader transformation of Muslim women’s political agency in contemporary Muslim democracies. This study aims to compare the roles, strategies, and policy impacts of female Muslim legislators in Indonesia and Turkey by examining how they navigate religious discourse, party structures, and political constraints while advocating for gender-inclusive reforms. The research seeks to identify convergences and divergences in their legislative behavior, institutional challenges, and use of Islamic arguments in political debates. A qualitative comparative political analysis was conducted using parliamentary documents, policy archives, and twenty semi-structured interviews with legislators, political advisors, and civil-society actors from both countries. The analysis employed thematic coding and cross-case comparison to evaluate how religious identity intersects with political participation and legislative outcomes. Findings reveal that Indonesian female Muslim legislators tend to mobilize pluralist Islamic narratives and civil-society alliances to strengthen gender advocacy, whereas their Turkish counterparts often navigate more centralized party systems and heightened ideological polarization. Both groups, however, strategically employ Islamic ethical frameworks to legitimize gender-inclusive policies. The study concludes that female Muslim legislators play a crucial role in transforming gender governance in Muslim-majority democracies, though the extent of their influence remains shaped by national political structures.